(untitled) (Scientia Agricola, 2001)
The purpose of this research was to define the centesimal composition of six lettuce cultivars (Aurora, Brisa, Lívia, Mimosa, Regina and Verônica) using four nutrient solutions. The experimental design was carried out in Santa Maria, RS, Brazil, consisting of entirely randomized subdivided parcels. The used spacing was 0.18 m between array and 0.25 m among plants. It was observed that the Ueda solution should not be used for the lettuce production in NFT system, due to the high dry mass production and, consequently, high caloric value, content of lipids and fibers, depreciating the quality of the final product, in spite of its low nitrate content. The lettuce production in the NFT system using the Castellane-Araújo, Furlani and Bernardes solutions maintained the nutricional quality (protein, ethereal extract and fiber, mineral residue contents) equivalent to the lettuce produced in soil, but presenting smaller caloric value. Therefore, the hydroponic lettuce is a healthy food for maintaining and improving its centesimal composition for being a product of low caloric value, easy cleaning and high durability.